Historicidade da tríade PAIC, SPAECE E SAEF: efeitos da retroalimentação das avaliações em Fortaleza/CE - Lopes, Afonso Filho Nunes (Universidade do Vale do Rio dos Sinos, 2024)
The subject of this thesis is the historicity of feedback from the Ceará Permanent System for Evaluation of Basic Education (SPAECE) in its SPAECE-Alfa strand; the Literacy at the Right Age Program (PAIC) , in the structuring axis of the External Evaluation and the Elementary Education Evaluation System (SAEF). The objective was to investigate how the systems/ subsystems evaluation and/ or monitoring/ monitoring, or rather, how management models affect the construction of educational and evaluation processes of the municipal public network of Fortaleza, in the period from 2007 to 2023. For this, the methodology adopted was based on a documentary approach - focusing on the analysis of newspaper headlines, excerpts from newsletters and reports produced by SAEF, which constituted the empirical corpus. I considered the documents as monuments (Le Goff, 1996). This made it possible to argue about the way in which the constitution of the school network of Fortaleza and how the two major administrative restructurings were organized and presented by social media that allowed me to interlace and discuss about the systems/ subsystems that act in the public schools of Fortaleza in the light of neoliberal rationality (Dardot; Laval, 2016) and the management of education (Laval 2019), where evaluative delusions (Veiga-Neto, 2000), through large-scale external evaluation systems, leverage the reformist discourses in education. I defend the thesis that the (sub)systems of evaluation and/or monitoring/ follow-up, inserted in the context of the municipal public education network of Fortaleza, are fundamental to the city and exert value to the conception of quality of education, defended by these initiatives. However, the effects of its application, especially when they are considered the main inducer of the educational evaluation process, endorse the ideology of neoliberal rationality. Therefore, the thesis argues and explores the relationship between evaluation and monitoring systems, performativity, quality of education and accountability of school managers in the context of municipal public education in Fortaleza.
Keywords: Avaliação externa; PAIC; SPAECE-Alfa; SAEF; (Sub)sistemas; External evaluation; Subsystem; ACCNPQ::Ciências Humanas::Educação